2015
DOI: 10.1039/c5ra02205c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and tensioactive properties of PEO-b-polyphosphate copolymers

Abstract: Investigation of the micellization of degradable polyphosphoester based surfactants following a solvent-free process: the role of the pendent chain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 37 publications
2
22
2
Order By: Relevance
“…Indeed, this work pays attention to amphiphilic diblock copolymers made up of hydrophilic PEG and hydrophobic PPE blocks. These copolymers are prone to self-assemble into nanoparticles in water [ 22 , 23 ] which makes them very attractive for drug delivery applications. In a previous work, we demonstrated that increasing the length of the PPE substituent from ethyl to heptyl favorably impacts the size and stability of the nanoparticles [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, this work pays attention to amphiphilic diblock copolymers made up of hydrophilic PEG and hydrophobic PPE blocks. These copolymers are prone to self-assemble into nanoparticles in water [ 22 , 23 ] which makes them very attractive for drug delivery applications. In a previous work, we demonstrated that increasing the length of the PPE substituent from ethyl to heptyl favorably impacts the size and stability of the nanoparticles [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In line with ROP of lactones that can be initiated from macroinitiator such as monomethoxypoly(ethylene oxide) (PEO) to prepare diblock copolymers such as PEO‐ b ‐PLA or PEO‐ b ‐PLGA, similar diblock copolymers, PEO‐ b ‐PPE, of well‐controlled composition can be obtained by organocatalyzed ROP in presence of the selected PEO macroinitiator …”
Section: Synthesis: Organocatalyzed Ring‐opening Polymerizationmentioning
confidence: 99%
“…By this reaction, a range of cyclic phosphotriester having R′ = H and various R groups that include alkyl chains of various size (methyl to octyl) and unsaturated chains (allyl, butenyl, butynyl, acrylate) has been obtained in good purity enough to be polymerized by the ROP process. However, the purification of these monomers that are highly sensitive toward traces of water or other protic species that easily open the ring, remains a tedious step.…”
Section: Synthesis: Organocatalyzed Ring‐opening Polymerizationmentioning
confidence: 99%
See 2 more Smart Citations